Influence of glutathione S‐transferases (GSTM1, GSTT1, and GSTP1) genetic polymorphisms and smoking on susceptibility risk of chronic myeloid leukemia and treatment response. Issue 7 (20th May 2019) - Rostami, Golale; Assad, Dlnya; Ghadyani, Fatemeh; Hamid, Mohammad; Karami, Amirhossien; Jalaeikhoo, Hasan; Kalahroodi, Ramezan Ali
Abstract: Background: Glutathione S‐transferases (GSTs) polymorphisms may impact on chronic myeloid leukemia (CML) risk or heterogeneous responses to Imatinib mesylate (IM). The aim of this study was to evaluate the correlation between GSTs polymorphisms and CML risk, treatment response. Methods: We genotyped GSTM1, GSTT1 null deletion polymorphisms, and GSTP1 Ile105Val polymorphism by PCR methods and BCR‐ABL transcripts were analyzed by qRT‐PCR in 104 CML patients and 104 sex‐ and age‐matched healthy individuals. Results: Individual analysis showed significant association of GSTM1 ( p  = 0.008; OR = 0.46; 95% CI: 0.26–0.82) and GSTP1 genes ( p  = 0.04; OR = 1.56; 95% CI: 1.016–2.423) with CML risk. The combined analysis indicated that GSTM1 null/GSTT1 present, GSTM1‐null/GSTP1M*(AG/GG) as well as GSTT1 present/ GSTP1M* genotype were associated with CML risk (ORg(‐):2.28; 95% CI: 1.29–4.04; ORgg: 2.85; 95% CI: 1.36–5.97; OR(‐)g: 1.75; 95% CI: 0.99–3.06, respectively). The proportion of CML cancer attributable to the interaction of smoking and GSTM1 null, GSTT1null, and GSTP1 M* was 42%, 39%, and 13%, respectively. Patients with GSTM1‐null and GSTP1 AG/GG genotype had significantly a lower rate of MMR achievement ( p  = 0.00; p  = 0.009 respectively). Event‐free survival (EFS) percentage was similar between GSTM1 null and GSTM1 present patients ( p  = 0.21). Conclusion: Our study suggests the influence of GSTM1 and GSTP1 polymorphisms on CML risk and treatment response. The interaction between GSTs polymorphisms and smoking plays a significant role on CML susceptibility.